S10 The Impact of Omalizumab on Lung Function and Quality of Life in Patients with Severe Allergic Asthma in UK Clinical Practice: A multi-centre prospective observational study – APEX II. (12th November 2015) - Niven, R; Kurukulaaratchy, R; Heaney, L
Abstract : Background: A previous retrospective UK study (APEX I) demonstrated omalizumab significantly reduced oral corticosteroid (OCS) use, exacerbations, lung function and quality of life (QoL in severe allergic asthmatic (SAA) patients. Aim: This multi-centre observational study was conducted to confirm the observed retrospective findings prospectively. Methods: Retrospective data were collected 12 months prior to and prospective data were collected 12 months following omalizumab initiation in SAA patients ≥16 years. The primary endpoint was the change in mean daily oral corticosteroid (OCS) dosage. Secondary endpoints included changes in lung function, ACT and AQLQ scores and missed days in education/work and employment in the 12 months pre and post omalizumab initiation. Results: 258 patients were enrolled from 22 UK centres (January 2012–February 2015); mean age 44.7 years (±SD 14.2), 65% females, mean asthma duration 25.1 years (±SD 15.1) For the ITT population (n = 235), 82.4% of patients were classified as responders. At 12 months, mean daily OCS dose significantly decreased by 16% from 10.3 mg/day (±7.1) to 8.7 mg/day (±8.6) (n = 211, p < 0.001) and 61.6% of patients stopped OCS or reduced OCS dose by ≥20%. The mean (±SD) FEV1 significantly increased from 66.9% (±19.35%) to 71.3% (±20.9%) in the 12 months post compared to pre- omalizumab initiation (p < 0.001 n = 118). Comparing the 12 months periods prior to and following initiation of omalizumab, the mean ACT score improved from 9.8 (±4.3) to 14.4 (±5.7) (n = 162, p < 0.001) and the mean AQLQ score improved from 3.2 (±1.3) to 4.4 (±1.5) (n = 161, p < 0.001). There was a significant decrease in missed days from work/education following omalizumab initiation (12 months pre-omalizumab: 14.65 days; 12 months post-omalizumab 6.22 days with p < 0.01; n = 63). For 93 patients unemployed/not in education at the study start, 72 were unemployed/not in education at study end. Conclusions: The data prospectively confirm that omalizumab is associated with significant reduction in OCS use, lung function, ACT, AQLQ and days missed from work/education.